Tradizione e traduzione. Il De Pallio di Tertulliano - Campus, Alessandro (TranScript)
In the short work De Pallio Tertullian reports the Christian use of the pallium to the Carthaginian tradition, showing how the construction of Christian identity is also based on pre-Roman tradition. The autoethnography that Tertullian carries out in this treatise shows how he tries to insert the new religion within the North African cultural heritage, reevaluating the ancient non-Roman traditions, within the framework of the cultural rearrangement of the post-Punic identity horizon. Finding a new meaning to one’s life means reformulating one’s identity in dialectical terms. In the chronological scansion of anamnesis, diagnosis, prognosis, that is, of past, present, future, there is no doubt that the negotiation between the different moments serves to structure identity.